Physical exercise, depression, and anxiety in 2190 affective disorder subjects - D'Angelantonio, Michele; Collins, Joanna L.; Manchia, Mirko; Baldessarini, Ross J.; Tondo, Leonardo (Journal of affective disorders, 2022)
This study evaluated associations of PE with symptomatic status in mood and anxiety disorder subjects, and considered many other associated factors so as to expand on comparable previous studies. Consenting adults at a mood disorder center were assessed for associations of PE frequency ([never, past only, ≤once/week] vs. regularly at 2–3- or >3-times/week) with standard psychometric measures of depression and anxiety symptoms, selected demographic, clinical factors, using bivariate and multivariate methods. Of 2190 subjects (58.8% women; mean age 42.6 years; 44.8% with major depressive, 40.6% bipolar, and 14.6% anxiety disorders), 22.5% currently engaged in regular PE. Such engagement was associated with lower morbidity ratings, youth, male sex, being unmarried, more education, higher socio-economic status (SES), less religious practice, less early abuse, younger age at illness onset and at intake, fewer years ill, lower BMI, fewer siblings, hyperthymic temperament, less time depressed before intake, and living at higher population density. Greater PE-frequency was associated with lower ratings of depression (but not anxiety), male sex, younger age, and lower BMI. Factors independently associated with PE in multivariate modeling ranked by significance: older age at intake ≥ lower BMI > more education > higher SES > male sex. PE assessment did not include type, intensity or duration. Some information provided may be subject to recall bias, though it should not affect comparisons among subjects. Regularly repeated PE again appeared to be beneficial for patients with depression or anxiety and should be included in their treatment interventions. •Physical exercise (PE) and its frequency were inversely associated with depression and anxiety severity scores.•PE was plausibly associated with several socio-demographic and clinical variables.•Factors independently associated with lack of or low PE were: older age > high BMI > less education > low socio-economic status > female sex